ANALYSIS OF STUDENT'S ABILITY TO SOLVE MATHEMATICAL LITERACY PROBLEMS IN JUNIOR HIGH SCHOOLS IN THE CITY AREA - Yulyanti Harisman; Dwita Elfri Mayani; Armiati Armiati; Hamdani Syaputra; Mohd Hasril Amiruddin (IKIP Siliwangi and I-MES, 2023)
Mathematical literacy problems require counting and solving mathematical problems in daily life. This study aims to analyze the ability of junior high school students to solve mathematical literacy problems. This qualitative research uses a case study approach with the subject of 15 junior high school students in the city area. The instrument in this study is six mathematical literacy questions oriented to PISA test questions and interview guidelines. The data analysis technique in this study is thematic analysis. This study's results show three groups of students' abilities in solving mathematical literacy problems based on their initial abilities: Time Stone, Power Stone, and Mind Stone